2006
DOI: 10.1111/j.0014-3820.2006.tb01230.x
|View full text |Cite
|
Sign up to set email alerts
|

Does Size Matter Most? The Effect of Growth History on Probabilistic Reaction Norm for Salmon Maturation

Abstract: Abstract. Body size is widely believed to affect the occurrence of sexual maturation. Recent studies have used changes in the age-specific body size at which the probability of maturing is 50%, a feature of probabilistic reaction norms, to quantify purported evolution of life histories. However, body size results from a combination of growth rates during successive developmental stages. Therefore, to understand the evolution of the maturation schedule, it is necessary to comprehend the relationships among body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
85
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(91 citation statements)
references
References 54 publications
6
85
0
Order By: Relevance
“…This result coincides well with the report by Morita and Fukuwaka (2006). They estimated growth history from annuli of scales in hatchery-arrived chum salmon, and showed that the recent growth rate is the most important factor for oceanic fish to determine whether mature or not mature in the subsequent spawning period.…”
Section: Discussionsupporting
confidence: 91%
“…This result coincides well with the report by Morita and Fukuwaka (2006). They estimated growth history from annuli of scales in hatchery-arrived chum salmon, and showed that the recent growth rate is the most important factor for oceanic fish to determine whether mature or not mature in the subsequent spawning period.…”
Section: Discussionsupporting
confidence: 91%
“…2), supporting the view that reduced reproductive investment was not only a response to strengthening natural selection but also related to increased life expectancy. Finally, somatic body condition had a positive effect on investment (significant on gonad weight and egg number) ( Table 1), confirming that surplus energy gained before reproduction plastically affects energy allocation to reproduction (23).…”
Section: Resultsmentioning
confidence: 61%
“…Importantly, we have accounted for the plastic effect of short-term variation in growth conditions in our reaction norm approach. Indeed, in teleosts plasticity in reproductive decisions is affected by the rate of surplus energy gained during critical periods (23). In Windermere pike, energy used for reproduction in March and April is gained during the previous summer (15).…”
Section: Discussionmentioning
confidence: 99%
“…We used the annual scale growth between the first and third winters at sea to represent cumulative early growth because Morita and Fukuwaka (2006) found that growth during the second and third year at sea best predicted the probability of maturation for chum salmon.…”
Section: Growth Pattern Implication On Age Of Maturationmentioning
confidence: 99%